Rotational energy as a measure of flow swirl intensity - Shishkin Nickolay (E3S Web of Conferences)
The paper proposes a criterion for estimating the intensity of swirling flow using Mach number for the rotational component of velocity. The drop in the maximum value of the criterion in the case of jet propagation in a pipe and in the case of mixing in a confined swirling flow is analyzed. The approximating dependences of the decrease of the swirling intensity according to the experimental works of different authors have been obtained.